Nonocclusive mesenteric ischemia: fulminant pancolitis - Kato, Kazuya (Clin Case Rep, 2016)
NOMI is mesenteric hypoperfusion with reactive vascular spasms. Changes in the color of the mucosa may reflect the severity of the ischemia of the colon and the severity of prognosis. Even with surgery, the mortality rate is 75%. Diagnosis requires a high degree of clinical suspicion.